2016
DOI: 10.2208/jscejhe.72.i_1081
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dynamics of River Channel and Vegetation in Gravel Bed River

Abstract: In this study, we developed the vegetation prevalence model. This model takes into account the existence/nonexistence of vegetation and the resistance of willows above ground and their root systems to flowing water and sediment transport at different tree growth stages. The growth increment regarding various parts of a willow tree is estimated on the basis of the tree age. In the model, willows' resistance to flowing water and sediment transport is varied with time to simulate each growth stage. The vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Each flood had a typical duration for a mountainous region. Maximum discharge was 300 m 3 /s, which matched the average peak of the Satsunai River in Japan (Nagata et al 2016). Related parameters for the numerical simulation are summarized in Table 2.…”
Section: Simulation Scenarios and Parametersmentioning
confidence: 76%
“…Each flood had a typical duration for a mountainous region. Maximum discharge was 300 m 3 /s, which matched the average peak of the Satsunai River in Japan (Nagata et al 2016). Related parameters for the numerical simulation are summarized in Table 2.…”
Section: Simulation Scenarios and Parametersmentioning
confidence: 76%
“…The authors have reported several ways for estimating the dynamic vegetation effects (i.e. Asahi et al ., ; Uchida et al ., ; Nagata et al ., ; Kang et al ., ), although this approach has not yet been incorporated into the iRIC Nays2DH model.…”
Section: Macroscale: Channelsmentioning
confidence: 96%
“…The authors have reported several ways for estimating the dynamic vegetation effects (i.e. Asahi et al, 2013;Uchida et al, 2015;Nagata et al, 2016;Kang et al, 2018), although this approach has not yet been incorporated into the iRIC Nays2DH model. Jang and Shimizu (2007) compared channel evolution without and with vegetation by means of the laboratory experiments and computational simulation as shown in Figures 27 and 28.…”
Section: Vegetation Effects On Channel Morphologymentioning
confidence: 99%
“…Where, 𝐴: The projected area of the tree, which is assumed to be (0.75 × 𝐻 3 × canopy width). 𝐶 𝑑𝑓 : the drag coefficient of the tree under the water load, which is assumed to be 1.0 10) . 𝐶 𝑑𝑤 : the drag coefficient of the tree under the wind, which is assumed to be 1.0 when the wind speed is less than 5.25m/s 12) .…”
Section: Calculating the Displacement Of Treementioning
confidence: 99%
“…Therefore, it is urgently necessary to study the mechanism of riparian destruction during the simultaneous occurrence of floods and storms. As for the relevant studies, wind damage to the tree was discussed in the forestry field [4][5][6] , and flood damage to the tree was discussed in river engineering [7][8][9][10] , there is few research about the simultaneous effect of flood and wind on the destruction of the riparian tree.…”
Section: Introductionmentioning
confidence: 99%